FROM TRAGEDY TO ‘CRIP’ TO HUMAN: THE NEED FOR MULTIPLE UNDERSTANDINGS OF DISABILITY IN PSYCHOTHERAPY - Roosen, Kaley Maureen (Critical Disability Discourses, 2009)
Individuals with disabilities have been largely ignored from research and training in the field of Psychology. Historically, when disability is discussed in psychotherapy theory, it is often pathologized as a condition that contributes to a maladaptive personality and poor societal functioning. The following research paper proposes a new understanding of disability in the field of Psychology through the introduction of a disability-affirmative model. Through understanding disability expansively as an extension of the human condition, a distinct minority group, a rich and valued culture, and as a bodily experience, Psychology can best contribute to the diverse lives of those with disabilities. Furthermore, by adopting a more flexible and positive view of disability, Psychology will be more open to the innovative and valued ideas presented both from professionals with disabilities and individuals within Critical Disability Studies in research, practice, and training.